What happens to racial and ethnic minorities after cancer surgery at American College of Surgeons National Surgical Quality Improvement Program hospitals? - Parsons, Helen M; Habermann, Elizabeth B; Stain, Steven C; Vickers, Selwyn M; Al-Refaie, Waddah B (Journal of the American College of Surgeons, 2012)
Inadequate access has contributed to widespread racial disparities in cancer care in the United States. However, the outcomes for racial minorities at quality-seeking hospitals, such as those participating in the American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP), remain unknown. We hypothesized that operative outcomes for racial and ethnic minority patients after cancer surgery at ACS NSQIP hospitals are comparable with those for white patients. Using the 2005-2008 ACS NSQIP data, we identified 38,926 patients who underwent thoracic, abdominal, or pelvic cancer surgery. We used multivariate logistic regression to examine the association between race and ethnicity and short-term (30-day) operative outcomes after cancer surgery. Sensitivity analyses were performed to ensure the relationship remained consistent after stratification by procedure. Nonwhite patients constituted 16.9% of patients treated for cancer surgery in ACS NSQIP hospitals. Although nonwhite patients were more likely to have higher levels of comorbidities and undergo more complex resections (p < 0.05 for all), multivariate analyses demonstrated that these patients were as likely as white patients to have adverse short-term operative outcomes develop after cancer surgery. These results persisted after stratification by extent of surgical procedure. However, black, Hispanic, and American-Indian/Alaskan-Native patients were more likely to experience prolonged length of stay (odds ratio for black vs white patients = 1.33; p < 0.001). Racial and ethnic minority patients who undergo their cancer surgery at ACS NSQIP hospitals have short-term operative outcomes similar to white patients, but they remain hospitalized longer. These findings suggest that access to quality-driven hospitals might ameliorate racial disparities in cancer care and outcomes. Future policies should focus on expanding access to quality-driven surgical facilities as a step toward timely and optimal cancer care.